1974
DOI: 10.1111/j.1471-4159.1974.tb04361.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Tryptophan and 5‐ht Metabolism in the CNS of the Newborn Rat

Abstract: —The relationships between plasma tryptophan and 5‐HT metabolism in the CNS were studied in newborn rats and compared with adults. Both the concentration of free tryptophan in plasma and that of the amino‐acid in brain were much higher immediately after birth than later on. Drugs such as salicylate and chlordiazepoxide, which increased brain tryptophan concentrations in adults by displacing the plasma amino acid bound to serum albumin, were ineffective in newborn rats: most of the amino acid being already free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 25 publications
4
31
1
Order By: Relevance
“…tryptophanan hydroxylase, 5-hydroxytryptophan-decarboxylase) approa ches the adult level at birth. However, per haps because of a turnover rate in the neo nate which surpasses that in the adult, trypto phan injection (100 mg/kg) in our studies caused only a slight increase in the 5-HT of neonatal brain [2,36], In addition, L-tryptophan administration did not influence the swimming ability of newborns. However, be ginning with the 3rd postnatal day, when this amino acid precursor has been reported to in crease brain 5-HT content dramatically, in jection of 100 mg/kg of tryptophan resulted in a shortened latency to swimming and increas ed number of FS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…tryptophanan hydroxylase, 5-hydroxytryptophan-decarboxylase) approa ches the adult level at birth. However, per haps because of a turnover rate in the neo nate which surpasses that in the adult, trypto phan injection (100 mg/kg) in our studies caused only a slight increase in the 5-HT of neonatal brain [2,36], In addition, L-tryptophan administration did not influence the swimming ability of newborns. However, be ginning with the 3rd postnatal day, when this amino acid precursor has been reported to in crease brain 5-HT content dramatically, in jection of 100 mg/kg of tryptophan resulted in a shortened latency to swimming and increas ed number of FS.…”
Section: Discussionmentioning
confidence: 97%
“…catecholaminergic and serotonergic neuronal system in the neonatal rat brain are at differMorphological and biochemical evidence ent maturational levels which have been in the literature has demonstrated that the characterized by regional and developmental differences in functional properties [2,5,6,19,24,36,37]. The early postnatal develop ment of monoaminergic systems is well de fined; however, less is known about the role of these systems in the ontogenesis of certain behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…As heparin has been shown to decrease tryptophan binding to albumin, serum was used for tryptophan measurement (9). Free and bound tryptophan were immediately separated by ultrafiltration (Amicon Centrifree ultrafilter) using fixed angle rotor centrifugation at room temperature for 20 min at 2000 X g. Total Trp concentrations in serum and free Trp in ultrafiltrates were measured immediately by an adaptation of an HPLC isocratic method with fluorometric detection as previously de-369 scribed (4,10).…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected into heparinized tubes with 25 iu heparin per ml of blood, a concentration which does not affect plasma Trp disposition (Bourgoin et al, 1974). The blood was then centrifuged and the resulting plasma separated into two portions.…”
Section: Plasma Metabolite Measurementsmentioning
confidence: 99%
“…This mechanism is largely involved during tryptamine (5-HT) depends on the concentration of ontogenesis (Bourgoin et al, 1974), food deprivation tryptophan (Trp), its precursor (Eccleston et al, 1965). (Knott & Curzon, 1972) or after immobilization Since tryptophan hydroxylase is normally un- (Knott & Curzon, 1972).…”
Section: Introductionmentioning
confidence: 99%